Eugenol inhibits quorum sensing and biofilm of toxigenic MRSA strains isolated from food handlers employed in Saudi Arabia - Nasser Abdulatif Al-Shabib (Biotechnology & Biotechnological Equipment, 2017)
Food handlers are important component in assessment and maintenance of food quality as they are carriers of food pathogens causing spoilage. Food spoilage is attributed to quorum sensing (QS) controlled development of biofilms. Therefore, there is an urgent need to develop novel QS and biofilm inhibitors to prevent spoilage of food products. In the present study, toxin producing biofilm forming methicillin-resistant Staphylococcus aureus (MRSA) were isolated from food handlers. Further, eugenol was screened for its QS and anti-biofilm properties. Analysis of nasal and hand swabs revealed the presence of seven toxigenic and biofilm forming MRSA strains. Eugenol demonstrated significant anti-QS activity in CVO26 and also reduced the QS-regulated production of elastase, protease, chitinase, pyocyanin and exopolysaccharide (EPS) in PAO1 considerably. Eugenol demonstrated 17%–86%, 24%–69%, 30%–91%, 9%–94% and 4%–89% reduction in biofilm biomass of S. aureus ATCC 25923 and MRSA strains FSA3, FSA11, FSA13 and FSA32, respectively. Sub-inhibitory concentrations of eugenol also decreased the metabolic activity in biofilm cells. Molecular docking analysis showed high binding affinity of eugenol that represents its biofilm inhibitory activity. This is the first report on the carriage of toxigenic drug-resistant biofilm forming S. aureus by food handlers and inhibition of their biofilms in the Kingdom of Saudi Arabia. The findings give a clear insight into the food safety hazards associated with the carriage of S. aureus and present eugenol as a broad-spectrum anti-QS and anti-biofilm agent.